1996
DOI: 10.1007/bf02523837
|View full text |Cite
|
Sign up to set email alerts
|

Lipidic characterization of full‐grown amphibian oocytes and their plasma membrane‐enriched fractions

Abstract: The content and composition of neutral lipids and phosphoglycerides from full-grown prophase-arrested Bufo arenarum Hensel oocytes and from their ghost preparations were studied. The ghosts obtained are highly enriched in plasma membrane as suggested by the activity of 5'-nucleotidase, a marker enzyme, and the level of typical membrane components such as sphingomyelin, phosphatidylserine (PS), phosphatidylinositol (PI), and phosphatidic acid. In whole oocytes, triacylglyceride (TAG) comprises about 60% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In zebrafish, Lister & Van Der Kraak (2008) showed that follicles expressed enzymes that were involved in AA release, such as phospholipase A 2 (PLA 2 ) and phospholipase C γ1 , or enzymes that can metabolize AA such as COX 1 , COX 2 and prostaglandin synthase-2. In agreement with this finding, it was shown in Rhinella arenarum that P 4 -induced maturation caused significant changes in the amount and composition of phospholipids and neutral lipids in both fully grown ovarian oocytes and plasma membrane-enriched fractions (Caldironi & Alonso, 1996; Mata et al ., 2000; Zelarayán et al ., 1999). These changes may occur due to lipolytic enzymes activation, especially PLA 2 , that release AA.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In zebrafish, Lister & Van Der Kraak (2008) showed that follicles expressed enzymes that were involved in AA release, such as phospholipase A 2 (PLA 2 ) and phospholipase C γ1 , or enzymes that can metabolize AA such as COX 1 , COX 2 and prostaglandin synthase-2. In agreement with this finding, it was shown in Rhinella arenarum that P 4 -induced maturation caused significant changes in the amount and composition of phospholipids and neutral lipids in both fully grown ovarian oocytes and plasma membrane-enriched fractions (Caldironi & Alonso, 1996; Mata et al ., 2000; Zelarayán et al ., 1999). These changes may occur due to lipolytic enzymes activation, especially PLA 2 , that release AA.…”
Section: Introductionsupporting
confidence: 69%
“…In starfish, arachidonic acid (AA) and eicosapentaenoic acid were capable of inducing maturation. In agreement with this finding, it was shown in Rhinella arenarum that P 4 -induced maturation caused significant changes in the amount and composition of phospholipids and neutral lipids in both fully grown ovarian oocytes and plasma membrane-enriched fractions (Caldironi & Alonso, 1996;Mata et al, 2000;Zelarayán et al, 1999). PUFAs appear to be involved in the mechanism by which methyladenine induces oocyte maturation (Meijer et al, 1986).…”
Section: Introductionmentioning
confidence: 53%
“…The larger content of SM in stage IV and V oocytes with respect to stage III oocytes could be related to the above-mentioned role of this phospholipid in the maturation process that stage V oocytes may undergo. In full-grown B. arenarum and X. laevis oocytes, PC has the same abundant acyl groups (Alonso et al, 1987;Caldironi & Alonso, 1996). The PC/SM and total phospholipids/SM ratios in stage III oocytes are higher than the ratios found in stage IV and V oocytes.…”
Section: Resultsmentioning
confidence: 83%
“…Results are shown as mean values ± SD (mol%) from three independent samples for SFA (saturated fatty acids), MUFA (monounsaturated fatty acids) and PUFA (polyunsaturated fatty acids). Caldironi & Alonso (1996) reported that TAG from full-grown oocytes has the same main acyl groups. sise eicosanoids as prostaglandins, thromboxanes and leukotrienes and various hydroxyeicosatetraenoic acids and epoxyeicosatrienoic acids.…”
Section: Figurementioning
confidence: 99%
“…Thus, our data obtained using the α 1C-∆1633 subunit may not represent the expression of the channel moiety alone, and subunit interactions may still arise. That the expression system itself may affect Q 10 is also a possibility; however, the membrane lipid composition of defolliculated amphibian oocytes [4] is not greatly different from that of the cardiac sarcolemma (see [35]). Furthermore, as the channel voltage sensors reside on the α 1 subunit [14] and as V a and K a are affected by temperature, other critical domains may be involved in the activation process.…”
Section: Effects Of Temperature On Cloned Cachsmentioning
confidence: 99%